The Joint Vasculitis Registry in German-speaking countries (GeVas): subgroup analysis of 195 GCA patients - Wallmeier, Pia; Arnold, Sabrina; Tais, Arlette; Ihorst, Gabriele; Janoschke, Marco; Schubach, Fabian; Aries, Peer; Bergner, Raoul; Bremer, Jan Phillip; Görl, Norman; Gutdeutsch, Eva; Hellmich, Bernhard; et al. (Clinical and experimental rheumatology, 2024)
Objectives: Giant cell arteritis (GCA) is one of the most common forms of vasculitis. There is an abundance of studies which are conducted in a randomised controlled trial setting but limited with respect to cohort size and follow-up time. GeVas is the first large-scale registry for vasculitides in German-speaking countries that enables to evaluate this rare disease. Herein we focus on the subgroup of GCA patients including follow-up data up to one year. - Methods: GeVas is a prospective, web-based, multicentre registry for the documentation of organ manifestations, outcomes, and therapy regimens in vasculitides. Recruitment started in June 2019. By April 2023, 15 centres were initiated and have started to enrol patients. - Results: After 4 years, 195 GCA-patients were included in the registry, of which 64% were female and 36% were male. The average age was 76 years at the time of recruitment (IQR=69-82). Seventy-nine percent were included in the registry because of a newly diagnosed GCA and 21% because of a relapse. At the first assessment most of the patients (89%) described general symptoms. Thirty-one percent stated ocular symptoms. Cranial symptoms were documented in 78% of the cases. All patients were documented with immunosuppressive treatment at start, of whom 95% received prednisolone, 16% cyclophosphamide, 20% methotrexate, and 48% tocilizumab. After three months 62% and after one year 91% of the patients achieved remission. - Conclusions: Regarding demographics, clinical manifestations and diagnostics, our study showed a similar composition compared to other studies. However, our data differed in terms of treatment regimens.
Gesehen am 22.10.2025